In situ activated mesenchymal stem cells (MSCs) by bioactive hydrogels for myocardial infarction treatment. Issue 34 (29th July 2020) - Gao, Long; Yi, Min; Xing, Min; Li, Hekai; Zhou, Yanling; Xu, Qing; Zhang, Zhaowenbin; Wen, Zhanpeng; Chang, Jiang
Abstract : A novel bioglass composite hydrogel that in situ activates mesenchymal stem cells for the treatment of myocardial infarction. Abstract : Stem-cell therapy has been proved as a promising strategy for myocardial infarction (MI) treatment. However, the therapeutic efficacy is mainly limited by the cellular activity of transplanted mesenchymal stem cells (MSCs). In this study, a novel bioglass (BG)/γ-polyglutamic acid (γ-PGA)/chitosan (CS) hydrogel was obtained by in situ adding BG to stimulate the imine bond formation. And the effect of the composite hydrogel on MI therapeutic efficacy was evaluated in a rat acute myocardial infarction (AMI) model in vivo and the possible mechanism of the BG/γ-PGA/CS hydrogel for the stimulation of the intercellular interaction between MSCs and cardiomyocytes (CMs) was explored by a MSC and CM co-culture experiment in vitro . The implantation of the MSC loaded BG/γ-PGA/CS composite hydrogel in the mice AMI model showed a significant improvement in the therapeutic efficacy with improved cardiac function, attenuation of heart remodeling, reduced cardiomyocyte apoptosis and accelerated vascularization. The in vitro cell experiments demonstrated that the BG/γ-PGA/CS hydrogel activated the intercellular interaction between MSCs and CMs, which resulted in reduced cell apoptosis and enhanced angiogenesis. Silicate based bioactive hydrogels activated MSCs and cell–cell interactions in cardiac tissue after AMI and significantly enhanced the efficacy, which suggests that this bioactive hydrogel based approach is an effective way to enhance stem-cell therapy.